Effect of the application of Levasa (sugar cane must) on the production and quality of Agave Tequilana Weber - Arreola Tostado, Jesús Manuel; Montoya Jasso, Víctor Manuel; Arreola Nava, Jesús Manuel; Castillo Valdez, Ximena; Olivares Arreola, Edgar Adrián; Báez Pérez, Aurelio (Revista Mexicana de Ciencias Agrícolas, 2020)
The use of organic fertilizers in agricultural production is gaining importance today, given the need to improve soil fertility and make rational use of chemical fertilizers. The sugar cane must be a by-product generated from the industrial fermentation of the molasses obtained from the sugar cane (Levasa), to obtain and produce yeasts for baking. An experiment was established to evaluate the effect of Levasa application on the growth, production and quality of Agave tequilana Weber. Greater amount of Levaza can better development of the crop and increase production and quality of agave. Three increasing doses were evaluated: 5, 10 and 15 m3 ha-1 and two controls: one without application of fertilizers and the other as the farmer does. The trial was evaluated using a randomized block design with four replications. An analysis of the main components was made. The experiment was established in April 2018, in a 6-year-old agave plantation, one year prior to harvest. Performance components, N, P, K content and Brix degrees were evaluated. The Levasa application promoted the development and nutrition of the Agave tequilana Weber crop. The best results were obtained with the application of 10 and 15 m3 ha-1, which was reflected in greater length of the leaf (129 cm), width (11.8 cm) and thickness (1.7 cm) of the same, diameter of cone (49 cm), plant height (191 cm), cone length (53 cm) and therefore higher yield of jima (253 t ha-1) and percentage of degrees Brix (30), which implied a greater quantity of tequila with better quality. At the main components level, the most important variables were: jima yield, aerial dry weight, leaf thickness, cone diameter, plant height and cone length.